Effect of nanostructuring on picosecond acoustics in a Zr film. (28th October 2021) - Hazra, Soumitra; Gupta, Neeti; Conibeer, Gavin; Shrestha, Santosh; Kini, R N
Abstract: Using the picosecond ultrasonic technique, we studied the effect of the formation of nanocrystallites on the surface of a metal transducer film. We found that the velocity of sound and the elastic constant are enhanced due to the nanocrystalline structures. The acoustic echo's shape, resulting from the reflection of the acoustic pulse at the surface, is modified, and an echo with an asymmetric bipolar shape is obtained. The shape of the acoustic echo can be explained, taking into account the formation of nanocrystallites at the film's surface.